Photoluminescence of Eu3+-doped CaZrO3 red-emitting phosphors synthesized via microwave-assisted hydrothermal method - Costa Macedo, Wagner [UNESP]; Germano Bispo Junior, Airton [UNESP]; de Oliveira Rocha, Kleper [UNESP]; de Souza Albas, Agda Eunice [UNESP]; Pires, Ana Maria [UNESP]; Rainho Teixeira, Silvio [UNESP]; Longo, Elson (Elsevier, 2020)
Eu-doped 1, 3 and 5 % CaZrO3 red-emitting phosphors were synthesized for the first time using the microwave-assisted hydrothermal method followed by heat treatment at 1200 °C. After the crystallization, the orthorhombic CaZrO3 and the non-stoichiometric cubic Ca0.15Zr0.85O 1.85 phases were identified for all samples, and the portion of the non-stoichiometric phase increases as the Eu3+ concentration increases. The excitation spectra of the phosphors display Eu3+ f-f excitation bands (namely at 395 nm and 464 nm) and the Eu3+→O2- charge transfer band at 250 nm, confirming that the CaZrO3 host acts as sensitizer for the Eu3+ luminescence. Likewise, the emission spectra feature the typical Eu3+ emission within the red spectral region, displaying CIE color coordinates of (0.642; 0.332), (0.663; 0.330) and (0.668; 0.327) for the 1, 3 and 5 % doped samples, respectively, indicating high emission color purity. By using Eu3+ as spectroscopic probe, the high-resolution selective emission spectra (14 K) confirm that Eu3+ replaces Ca2+ and Zr4+ local sites in both CaZrO3 and the Ca0.15Zr0.85O1.85 phases. Finally, the high absolute emission quantum yield of the 3 %-doped phosphor found at 393 nm (0.29 ± 0.03) confirms its potential application as red-emitting phosphor, especially in rapid identification of latent fingerprints, security ink or as red-emitting coating of near-UV LEDs for WLED applications.
Keywords: Luminescence; Microwave-assisted hydrothermal method; Red-emitting phosphors; Solid-state lighting